Negative electrode material and preparation method thereof, negative electrode plate and battery
By using soft and hard carbon co-clad layer on the surface of the graphite negative electrode material to control the structural parameters of the material, the problem of insufficient fast charging and cycling performance of traditional graphite negative electrode materials is solved, and efficient lithium-ion battery performance is achieved.
Patent Information
- Application Number
- CN202411542548.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-07
AI Technical Summary
The existing graphite anode materials have shortcomings in fast charging and cycling performance, resulting in poor fast charging and cycling performance of lithium-ion batteries.
The composite graphite negative electrode material is coated with soft and hard carbon. By controlling the relationship between the thickness of the carbon coating layer, the ID/IG ratio, OI value and median particle size in the Raman spectrum, the structure and performance of the material are regulated. , to improve fast charging and cycle performance.
The high fast charging performance and long cycle performance of composite graphite negative electrode materials have been achieved, and the comprehensive performance of lithium-ion batteries has been significantly improved.
Smart Images

Figure CN119400828A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode material and a preparation method thereof, a negative electrode sheet and a battery. Background Art
[0002] Lithium-ion batteries have high energy density, long cycle life and excellent fast charging capabilities. They have become the main power technology in the fields of transportation and consumer electronics, and will play an increasingly important role in the future. Based on the growing demand for fast charging of advanced lithium-ion batteries in electric vehicles and consumer electronics, a lot of research has been done on the fast charging mechanism of lithium-ion batteries and improving their fast charging performance. At present, it is generally believed that graphite anode materials are still the main factor limiting the fast charging of lithium-ion batteries. In addition to fast charging capabilities, excellent graphite anode materials also need to have both high energy density and good high temperature performance.
[0003] In the related art, the patent with publication number CN111244401A discloses a hard carbon-coated graphite negative electrode material, a lithium-ion battery, and its preparation method and application, which uses a hard carbon source to carbon-coat a graphite substrate, and introduces additives during the coating process to improve the coating effect. The obtained hard carbon-coated graphite has good morphology and particle size distribution, and the lithium-ion battery prepared therefrom has excellent low-temperature rate performance. However, the hard carbon coating layer has many defects, which aggravates the side reactions between the hard carbon-coated graphite and the electrolyte, resulting in deterioration of the battery cycle performance. The button half-cell prepared using hard carbon-coated graphite has a capacity retention rate of only 94.2% after 300 cycles at a rate of 1C.
[0004] In view of this, based on people's higher requirements for the fast charging capability and cycle performance of graphite negative electrode materials, this application is specially proposed. Summary of the invention
[0005] In view of this, the present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a negative electrode material and a preparation method thereof, a negative electrode plate and a battery, which can alleviate the problem of poor fast charging ability and cycle performance of existing graphite negative electrode materials, and is conducive to improving the fast charging ability and cycle performance of negative electrode materials, and further conducive to improving the fast charging performance and cycle performance of batteries using the negative electrode material.
[0006] In order to solve the above technical problems, this application is implemented as follows:
[0007] According to one aspect of the present application, an embodiment of the present application provides a negative electrode material, the negative electrode material comprising a graphite core and a carbon coating layer coated on at least a portion of the surface of the graphite core, the carbon coating layer comprising soft carbon and hard carbon;
[0008] The thickness of the carbon coating layer is H;
[0009] In the Raman spectrum, the negative electrode material has a carbon characteristic peak D and a carbon characteristic peak G, and the peak intensity of the carbon characteristic peak D is D The peak intensity I of the carbon characteristic peak G G The ratio I D / I G is S;
[0010] The OI value of the negative electrode material is D OI ;
[0011] The median particle size of the negative electrode material is D v50 ;
[0012] H, S, D OI and D v50 satisfy:
[0013] 0.1≤H×S / D OI ×D v50 ≤1.
[0014] In addition, the negative electrode material according to the present application may also have the following additional technical features:
[0015] In some embodiments, the H, S, D OI and D v50 Satisfy: 0.2≤H×S / D OI ×D v50 ≤0.8.
[0016] In some embodiments, the H, S, D OI and D v50 Satisfy: 0.3≤H×S / D OI ×D v50 ≤0.7.
[0017] In some embodiments, the value range of H is 70nm to 150nm.
[0018] In some embodiments, the D v50 The value range is 6μm~14μm.
[0019] In some implementation modes, the value range of S is 10% to 20%.
[0020] In some embodiments, the D OI The value range is 2 to 7.
[0021] In some embodiments, the mass ratio of the soft carbon to the hard carbon is 10:1 to 2:1.
[0022] According to another aspect of the present application, an embodiment of the present application provides a method for preparing the negative electrode material as described above, the method comprising:
[0023] mixing graphite, a soft carbon precursor, and a hard carbon precursor to obtain a mixture;
[0024] granulating the mixture to obtain a preform;
[0025] The preform is carbonized and then crushed to a target particle size to obtain a negative electrode material.
[0026] In some embodiments, the soft carbon precursor includes at least one of coal tar pitch or petroleum pitch.
[0027] In some embodiments, the hard carbon precursor includes at least one of phenolic resin, polyacrylonitrile, chitosan, epoxy resin, sucrose or polyvinyl pyrrolidone.
[0028] In some embodiments, the mass ratio of the graphite to the soft carbon precursor is 20:2 to 20:4.
[0029] In some embodiments, the mass ratio of the graphite to the hard carbon precursor is 30:1 to 30:3.
[0030] In some embodiments, the granulation temperature is 200°C to 300°C.
[0031] In some embodiments, the carbonization temperature is 1000°C to 1300°C.
[0032] According to another aspect of the present application, an embodiment of the present application provides a negative electrode plate, the negative electrode plate comprising a current collector and a negative electrode film layer disposed on a surface of the current collector;
[0033] The negative electrode film layer includes the negative electrode material as described above or the negative electrode material prepared according to the above method.
[0034] According to another aspect of the present application, an embodiment of the present application provides a battery, which includes the aforementioned negative electrode material, or includes the negative electrode material prepared according to the aforementioned method, or includes the aforementioned negative electrode plate.
[0035] Implementing the technical solution of the present invention has at least the following beneficial effects:
[0036] In the embodiment of the present application, the negative electrode material provided includes a graphite core and a carbon coating layer coated on at least a portion of the surface of the graphite core, the carbon coating layer includes soft carbon and hard carbon, and the present invention defines the thickness of the carbon coating layer, the I D / I G, the relationship between the OI value of the negative electrode material and the median particle size of the negative electrode material. Therefore, the soft and hard carbon-coated composite graphite negative electrode material combines the advantages of the soft carbon coating layer and the hard carbon coating layer, and through the reasonable regulation of the negative electrode material particle size (or graphite particle size), crystal plane orientation, carbon coating layer thickness and disorder, the prepared composite graphite negative electrode material has both high fast charging performance and long cycle performance.
[0037] Therefore, the negative electrode material of the present invention is a composite graphite negative electrode material coated with soft and hard carbon, which can solve the problems of poor fast charging performance and poor cycle performance of traditional graphite negative electrode materials, and the cycle performance and fast charging performance of the battery assembled therefrom can be significantly improved.
[0038] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 Shown is a schematic structural diagram of the negative electrode material of an embodiment of the present invention.
[0040] Description of reference numerals:
[0041] 10-graphite core;
[0042] 20-carbon coating layer;
[0043] 210-soft carbon;
[0044] 220 - Hard Carbon. DETAILED DESCRIPTION
[0045] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.
[0046] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0047] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0048] As analyzed in the background technology of the present invention, traditional graphite negative electrode materials have the problems of insufficient fast charging performance and cycle performance. In the related technology, in the industrialized graphite modification method, in order to improve the fast charging performance of graphite, soft carbon or hard carbon is usually used to coat the surface of graphite, increase the disorder of the graphite surface, increase the lithium insertion active sites on the graphite surface, and reduce the charge transfer impedance of graphite, so as to achieve the purpose of improving the fast charging performance of graphite.
[0049] Hard carbon has a higher degree of carbon atom disorder than soft carbon. The surface disorder of graphite coated with hard carbon is higher, there are more lithium insertion active sites, and the fast charging performance is excellent. Correspondingly, more lithium insertion active sites will lead to the intensification of side reactions between graphite and electrolyte during charging and discharging, causing the battery cycle performance to deteriorate. The carbon atom disorder of soft carbon is lower than that of hard carbon. The surface disorder of graphite coated with soft carbon is lower, there are fewer lithium insertion active sites, and the effect of improving fast charging performance is limited. The lower degree of disorder also avoids excessive side reactions between graphite and electrolyte during charging and discharging, and the battery has better cycle performance.
[0050] Based on this, in order to take into account the good cycle stability of the soft carbon structure and the excellent fast charging capability of the hard carbon structure, the inventors of the present application set a carbon coating layer containing soft carbon and hard carbon on the surface of the graphite, that is, provided a composite graphite negative electrode material co-coated with soft and hard carbon, while controlling the thickness and disorder of the carbon coating layer, while ensuring its high fast charging capability, it also has good cycle stability.
[0051] Furthermore, the inventors have also found that the particle size of graphite affects the specific surface area of graphite and the diffusion path of lithium ions in the graphite particles. The larger the particle size, the smaller the specific surface area of the graphite, the fewer the active sites for lithium embedding on the surface, the longer the diffusion path of lithium ions in the graphite particles, and the worse the fast charging ability. At the same time, the larger the particle size, the fewer the side reactions between the graphite and the electrolyte, and the better the cycle performance. The smaller the particle size, the larger the specific surface area of the graphite, the more active sites for lithium embedding on the surface, the shorter the diffusion path of lithium ions in the graphite particles, and the better the fast charging ability. At the same time, the smaller the particle size, the more side reactions between the graphite and the electrolyte, and the poorer the cycle performance. Therefore, when the particle size of graphite is controlled within a reasonable range, it can have both excellent cycle stability and high fast charging performance of graphite.
[0052] Theoretically, in the surface structure of graphite, lithium ions can only be embedded into graphite particles from the end faces of graphite, and the number of end faces on the surface of graphite particles determines the number of "channels" available for lithium ion embedding. For highly oriented graphite, its surface is an anisotropic structure, and the number of end face structures on the surface is relatively small, which is not conducive to the rapid embedding of lithium ions, and the fast charging performance is poor. The surface of low-oriented graphite tends to be an isotropic structure, and the number of end face structures on the surface is relatively large, which can provide lithium ions for rapid de-embedding, and the fast charging performance is better. In view of this, the inventors selected low-oriented graphite aggregates and further reduced the orientation of the composite graphite by granulation. The prepared composite graphite achieves a macroscopic isotropic effect, which is conducive to the rapid embedding of lithium ions into graphite particles and has excellent fast charging performance.
[0053] Based on the above research, the inventors of this application have fully considered the characteristics of existing negative electrode materials such as graphite, soft carbon, and hard carbon, and provided a composite graphite negative electrode material co-coated with soft and hard carbon, which has both excellent fast charging performance and cycle performance. A method for preparing the negative electrode material, a negative electrode sheet containing the negative electrode material, and a battery containing the negative electrode material are also provided. The present application is described in detail below.
[0054] [Anode material]
[0055] See also Figure 1 As shown, in some embodiments, a negative electrode material is provided, which includes a graphite core 10 and a carbon coating layer 20 coated on at least a portion of the surface of the graphite core 10 , and the carbon coating layer 20 includes soft carbon 210 and hard carbon 220 .
[0056] In the present application, the negative electrode material is a composite graphite negative electrode material co-coated with soft and hard carbon, and the negative electrode material includes a graphite core 10 and a carbon coating layer 20 coated on at least the surface of the graphite core 10; that is, the provided negative electrode material is a core-shell structure, in which the core can be made of traditional graphite material, and the outer shell or shell layer, that is, the carbon coating layer 20, includes soft carbon 210 and hard carbon 220, which can provide excellent protection or improvement for the graphite core material.
[0057] It should be noted that the present invention does not limit the specific type or source of the graphite core, and the graphite core may be selected from various known graphite materials such as traditional natural graphite and artificial graphite.
[0058] In the present application, the term "coating" is not limited to direct coating, but also includes indirect coating. For example, the carbon coating layer 20 coats the graphite core 10, and there may be no other structure between the carbon coating layer 20 and the outer surface of the graphite core 10, or there may be one or more layers of other structures between the carbon coating layer 20 and the outer surface of the graphite core 10. Preferably, there is no other structure between the carbon coating layer 20 and the outer surface of the graphite core 10.
[0059] The carbon coating layer 20 is formed or coated on at least part of the surface of the graphite core 10, which can protect or improve the graphite core 10, and can be used to improve the structural stability of the negative electrode material, and improve the fast charging performance and cycle performance of the negative electrode material. The carbon coating layer 20 is formed or coated on at least part of the surface of the graphite core 10, which means that the carbon coating layer 20 can completely encapsulate the graphite core 10 in the coating layer, or the carbon coating layer 20 can only coat a part of the outer surface of the graphite core 10; that is, the carbon coating layer 20 can completely coat the graphite core 10, or it can coat a part of the surface of the graphite core 10, preferably completely coating.
[0060] In the present application, the thickness of the carbon coating layer 20 is H, and the unit of the thickness of the carbon coating layer is nm; in the Raman spectrum, the negative electrode material has a carbon characteristic peak D and a carbon characteristic peak G, and the peak intensity I of the carbon characteristic peak D is D The peak intensity I of the carbon characteristic peak G G The ratio I D / I G is S; the OI value of the negative electrode material is D OI ; The median particle size of the negative electrode material is D v50 , the unit of the median particle size of the negative electrode material is μm.
[0061] Furthermore, this application defines H, S, and D OI and D v50 The relationship between H, S, and D OI and D v50 Satisfy: 0.1≤H×S / D OI ×D v50 ≤1.
[0062] The inventors of the present application have found through extensive research during the material preparation process that the thickness of the carbon coating layer H on the surface of graphite, the I D / I G The value S, the OI value D of the negative electrode material OI , the volume median particle size D of the negative electrode material v50 , which is the main factor affecting the fast charging performance and cycle performance of soft and hard carbon-coated composite graphite anode materials. D / I G The value of, the OI value of the negative electrode material and the volume median particle size of the negative electrode material can make the negative electrode material have both high fast charging performance and long cycle performance.
[0063] In detail, when the thickness H of the carbon coating on the graphite surface is too thick, or the Raman spectrum I D / I G The value S is too large, or the OI value D of the negative electrode material OIToo small, or the volume median particle size D of the negative electrode material v50 Too small, resulting in H×S / D OI ×D v50 When the upper limit of exceeds 1, the cycle performance of the negative electrode material, that is, the composite graphite material, is poor. This is because, on the one hand, when the thickness H of the carbon coating layer is too thick, the amorphous carbon component on the graphite surface accounts for a high proportion. When the Raman spectrum I D / I G When the value S is too large, the graphite surface structure is highly disordered. Both will lead to a high degree of defect components on the graphite surface, more side reactions between graphite and electrolyte during the cycle, and poor cycle performance. On the other hand, when the OI value D of the negative electrode material (or graphite) is OI When the volume median particle size D of the negative electrode material (or graphite) is too small, the graphite surface is close to an isotropic structure, and the end surface structure of the graphite surface is more. v50 When the surface area of graphite is too small, it will be too large. Both will lead to an increase in the number of active sites on the graphite surface available for lithium ion embedding, and the corresponding defect components will also increase, which will also lead to an increase in side reactions between graphite and electrolyte during the cycle and deterioration of cycle performance.
[0064] When the thickness H of the carbon coating on the graphite surface is too thin, or the Raman spectrum I D / I G The value S is too small, or the OI value D of the negative electrode material OI Too large, or the volume median particle size D of the negative electrode material v50 Too large, resulting in H×S / D OI ×D v50 When the lower limit of is lower than 0.1, the fast charging performance of the negative electrode material, that is, the composite graphite, is poor. This is because, on the one hand, when the thickness H of the carbon coating layer is too thin, the proportion of amorphous carbon components on the graphite surface is low, and when the Raman spectrum I D / I G When the value S is too small, the disorder degree of the graphite surface structure is low. Both will result in fewer active sites on the graphite surface for lithium ion embedding, higher charge transfer impedance of graphite, and poor fast charging performance. On the other hand, when the OI value D of the negative electrode material (or graphite) is OI When the diameter is too large, the graphite surface tends to be anisotropic, and the end surface structure of the graphite surface is less. When the volume median particle size D of the negative electrode material (or graphite) is v50 When it is too large, the specific surface area of graphite is small. Both will result in fewer active sites on the graphite surface for lithium ion embedding, higher charge transfer impedance of graphite, and poor fast charging performance.
[0065] In summary, the inventors of the present application have found through a large number of experiments that the thickness H of the carbon coating layer on the graphite surface and the Raman spectrum I of the negative electrode material, i.e., the composite graphite D / IG Value S and the negative electrode material, that is, the OI value D of the composite graphite OI and the volume median particle size D of the negative electrode material, i.e. graphite v50 The four factors form a mutually restrictive relationship, jointly affecting the fast charging performance and cycle performance of graphite, and cannot be too large or too small at the same time.
[0066] Thus, the inventors of the present invention have found through a large number of studies that the thickness H of the carbon coating layer on the surface of graphite, the I D / I G The value S, the OI value D of the negative electrode material OI , the volume median particle size D of the negative electrode material v50 Satisfy 0.1≤H×S / D OI ×D v50 When ≤1, the electrochemical performance of the negative electrode material is better, which can make the comprehensive performance of the battery using the negative electrode material, such as lithium-ion battery, better, and at the same time have high fast charging performance and long cycle performance.
[0067] As an example, the above H×S / D OI ×D v50 Specifically, it can be any point value among 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, or a range value between any two of them.
[0068] In order to better balance the thickness H of the carbon coating on the graphite surface and the I D / I G The value S, the OI value D of the negative electrode material OI , the volume median particle size D of the negative electrode material v50 The relationship between the four, in some preferred embodiments of the present invention, the above H, S, D OI and D v50 Satisfy: 0.2≤H×S / D OI ×D v50 ≤0.8.
[0069] Further, in some preferred embodiments of the present invention, the above H, S, D OI and D v50 Satisfy: 0.3≤H×S / D OI ×D v50 ≤0.7.
[0070] By further optimizing H, S, D OI and D v50 The relationship between them can further improve the fast charging performance and cycle performance of the negative electrode material, thereby making the lithium-ion battery using the negative electrode material have both high fast charging performance and long cycle performance.
[0071] In some embodiments, the thickness H of the carbon coating layer ranges from 70 nm to 150 nm. As an example, H can be any one of 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, and 150 nm, or a range between any two thereof.
[0072] In the present application, the thickness of the carbon coating layer 20 determines the number of defects on the graphite surface, which directly affects the fast charging performance and cycle performance of the graphite. Therefore, the present invention designs the thickness H of the carbon coating layer of the negative electrode material to be 70-150 nm.
[0073] In some embodiments, the volume median particle size D of the negative electrode material is v50 The value range of is 6μm~14μm. As an example, D v50 It can be any point value among 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, and 14μm, or a range value between any two of them.
[0074] In this application, the volume median particle size reflects the average size of graphite particles, which affects the specific surface area of graphite and the diffusion path of lithium ions in graphite particles. Small-diameter graphite has excellent fast charging performance but poor cycle performance. Large-diameter graphite has excellent cycle performance but poor fast charging performance. Therefore, the present invention sets the volume median particle size D of the negative electrode material to v50 The design is 6μm~14μm, preferably 6μm~10μm.
[0075] In some embodiments, the I of the negative electrode material in the Raman spectrum D / I G The value S of is in the range of 10% to 20%. As an example, S can be any one of 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or a range between any two of them.
[0076] In this application, in the Raman spectrum of the negative electrode material, I D / I G It reflects the surface disorder of graphite particles. Graphite with higher surface disorder has excellent fast charging ability and poor cycle performance. Graphite with lower surface disorder has poor fast charging ability and better cycle performance. Therefore, the negative electrode material provided by the present invention, that is, the composite graphite particle Raman spectrum I D / I G The value S is 10% to 20%.
[0077] In some embodiments, the OI value D of the negative electrode material OI The value range of is 2 to 7. As an example, DOI It can be any point value among 2, 3, 4, 5, 6, 7, or a range of values between any two.
[0078] In the present application, the OI value indicates the crystal plane orientation of graphite particles. The lower the OI value, the lower the degree of graphite crystal plane orientation, the higher the degree of isotropy, and the more conducive to rapid charge and discharge. Therefore, the OI value of the negative electrode material provided by the present invention is D OI 2 to 7.
[0079] It should be understood that the present invention mainly controls the thickness of the carbon coating layer, the I of the negative electrode material in the Raman spectrum, and the D / I G The value of the negative electrode material, the OI value of the negative electrode material and the volume median particle size of the negative electrode material make the negative electrode material have both high fast charging performance and long cycle performance, wherein the combined use of soft carbon 210 and hard carbon 220 in the carbon coating layer can take into account the good cycle stability of the soft carbon 210 structure and the excellent fast charging capability of the hard carbon 220 structure, and the specific ratio of soft carbon 210 and hard carbon 220 can be selected and set according to actual conditions, and this application does not limit this.
[0080] Optionally, in the carbon coating layer, the mass ratio of the soft carbon 210 to the hard carbon 220 is 10:1 to 2:1, for example, 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, etc.
[0081] Therefore, based on the above research settings, the negative electrode material provided by the present invention is a soft and hard carbon coated composite graphite negative electrode material, which combines the respective advantages of the soft carbon coating layer and the hard carbon coating layer, and through reasonable regulation of graphite particle size, crystal plane orientation, carbon coating layer thickness and disorder, the prepared composite graphite negative electrode material has both high fast charging performance and long cycle performance.
[0082] In view of the fact that hard carbon-coated graphite has more defects on the surface, more active sites are available for lithium ion embedding, and better fast charging ability, it will also lead to aggravated side reactions between graphite and electrolyte, and poor cycle performance. On the other hand, soft carbon-coated graphite has fewer defects on the surface, fewer active sites are available for lithium ion embedding, poor fast charging ability, and fewer side reactions between graphite and electrolyte, and better cycle performance. The carbon coating layer of the composite graphite negative electrode material provided by the present invention contains both hard carbon 220 and soft carbon 210, and the composition and structure of the carbon coating layer are reasonably regulated, so that the fast charging performance and cycle performance of the prepared composite graphite negative electrode material reach a high level.
[0083] At the same time, in view of the important influence of the volume median particle size on the fast charging performance and cycle performance of the graphite negative electrode material. Graphite with smaller particle size has a larger specific surface area, and there are more side reactions between graphite and electrolyte during charging and discharging, and the cycle performance is poor. The lithium ion diffusion path in graphite particles with larger particle size is longer, which is not conducive to the rapid embedding of lithium ions into the particles, and the fast charging performance is poor. The composite graphite negative electrode material provided by the present invention has an appropriate particle size and can have both good fast charging and cycle performance.
[0084] Furthermore, since the crystal plane orientation reflects the degree of isotropy of the graphite negative electrode material, the graphite with a higher crystal plane orientation has a lower degree of isotropy, fewer end faces available for lithium ion embedding, and a poorer fast charging capability. In the preparation process of the composite graphite, the present invention selects low-oriented graphite as aggregate, and further reduces the graphite crystal plane orientation by composite granulation to obtain a composite graphite negative electrode material that is close to isotropy, and the prepared composite graphite negative electrode material has excellent fast charging performance.
[0085] [Method for preparing negative electrode material]
[0086] Accordingly, in some embodiments, the present application provides a method for preparing a negative electrode material, the method comprising the following steps:
[0087] mixing graphite, a soft carbon precursor, and a hard carbon precursor to obtain a mixture;
[0088] granulating the mixture to obtain a preform;
[0089] The preform is carbonized and then crushed to a target particle size to obtain a negative electrode material.
[0090] The preparation of the negative electrode material of the present invention can be carried out by first mixing graphite, a soft carbon precursor and a hard carbon precursor to obtain a mixture, then granulating the mixture at low temperature, and then carbonizing it at high temperature to obtain the negative electrode material. The preparation method of the negative electrode material provided by the embodiment of the present invention has simple process, convenient operation, strong feasibility, and is easy to realize industrial application.
[0091] It should be understood that all the features and advantages described above for the “negative electrode material” are also applicable to the “method for preparing the negative electrode material” and will not be described in detail here.
[0092] In some specific embodiments, the method for preparing the negative electrode material specifically includes the following steps S1 to S4:
[0093] S1. Prepare a mixture.
[0094] In step S1, preparing the mixture specifically includes: mixing graphite, a soft carbon precursor and a hard carbon precursor to obtain a mixture.
[0095] Optionally, in step S1, graphite, soft carbon precursor and hard carbon precursor can be mixed in a VCH mixer (high-efficiency mixing and modifying machine).
[0096] Optionally, in step S1, the soft carbon precursor may be selected from asphalt, such as, the soft carbon precursor includes but is not limited to at least one of coal tar pitch or petroleum pitch. For example, the soft carbon precursor may be coal tar pitch, or may be petroleum pitch, or may be a combination of coal tar pitch and petroleum pitch.
[0097] Optionally, in step S1, the hard carbon precursor can be selected from an organic polymer, such as, the hard carbon precursor includes but is not limited to any one or a combination of at least two of phenolic resin, polyacrylonitrile, chitosan, epoxy resin, sucrose or polyvinyl pyrrolidone. For the sake of brevity, the combinations within the above range are no longer listed one by one.
[0098] Optionally, in step S1, the mass ratio of graphite to the soft carbon precursor is 20:2 to 20:4, for example, 20:2, 20:3, 20:4, etc.
[0099] Optionally, in step S1, the mass ratio of graphite to the hard carbon precursor is 30:1 to 30:3, for example, 30:1, 30:2, 30:3, etc.
[0100] S2. preparing a preform.
[0101] In step S2, preparing the preform specifically includes: granulating the mixture to obtain the preform.
[0102] In the present application, in the process of preparing the preform, the mixture obtained in step S1 can be placed in a horizontal granulation kettle for low-temperature granulation to obtain the preform.
[0103] Optionally, in step S2, granulation is low-temperature granulation, and the temperature of low-temperature granulation is 200°C to 300°C. For example, the granulation temperature can be any one of 200°C, 220°C, 250°C, 260°C, 280°C, 300°C or a range between any two of them.
[0104] S3. Prepare semi-finished products.
[0105] In step S3, preparing the semi-finished product specifically includes: subjecting the preform obtained in step S2 to high-temperature carbonization in a tubular furnace in an inert atmosphere such as an argon atmosphere to obtain the semi-finished product.
[0106] Optionally, in step S3, the carbonization is high-temperature carbonization, and the temperature of the high-temperature carbonization is 1000°C to 1300°C. For example, the carbonization temperature can be any point value among 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1300°C or a range value between any two of them.
[0107] S4. Prepare negative electrode materials.
[0108] In step S4, preparing the negative electrode material body includes: crushing the semi-finished product obtained in step S3 into a target particle size and sieving to obtain the negative electrode material, that is, obtaining the soft and hard carbon coated composite graphite negative electrode material.
[0109] [Negative electrode]
[0110] Accordingly, in some embodiments, the present application provides a negative electrode plate, which includes a current collector and a negative electrode film layer arranged on the surface of the current collector; the negative electrode film layer includes the negative electrode material as described above or the negative electrode material prepared according to the above method.
[0111] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector. As an example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode film layer is disposed on two opposite surfaces of the negative electrode current collector. It is understood that the negative electrode film layer can also be stacked on any one of the two surfaces of the negative electrode current collector.
[0112] In the negative electrode sheet of the present application, the type of negative electrode current collector is not specifically limited and can be selected from the prior art according to actual needs, such as copper foil.
[0113] In some embodiments, in the negative electrode sheet, the negative electrode film layer includes the above-mentioned negative electrode material, a conductive agent and a binder.
[0114] In the above-mentioned negative electrode film layer, there is no particular limitation on the types of the conductive agent and the binder, as long as the purpose of the present application can be achieved, and they can be selected according to actual needs.
[0115] Optionally, in the negative electrode film layer, the mass ratio of the negative electrode material, the conductive agent and the binder is (70-90): (0.1-15): (0.1-15).
[0116] In the present application, the preparation of the negative electrode sheet can adopt various methods known in the prior art. For example, first prepare a negative electrode slurry containing a negative electrode material, a conductive agent and a binder, apply the negative electrode slurry on a negative electrode current collector, and obtain a negative electrode sheet after drying and other processes.
[0117] Among them, the specific preparation method of the negative electrode slurry can be selected from the prior art, and the present application is not limited. In some embodiments of the present application, the negative electrode slurry is prepared by the following method: 70% sodium carboxymethyl cellulose (CMC) and conductive agent conductive carbon black are added to deionized water, and stirred at low speed for 2 hours to form a conductive glue; the negative electrode material is added to the conductive glue, and the mixture is stirred at low viscosity and high speed for 1 hour to form a first mixed solution; styrene-butadiene rubber (SBR) is added to the first mixed solution, and the mixture is stirred at high viscosity and high speed for 1 hour to form a second mixed solution; ethanol and the remaining 30% of CMC powder are added to the second mixed solution, and the mixture is stirred at low viscosity and high speed for 2 hours to obtain a negative electrode slurry.
[0118] [Battery]
[0119] In some embodiments, the present application provides a battery, which includes the aforementioned negative electrode material, or includes the negative electrode material prepared according to the aforementioned method, or includes the aforementioned negative electrode plate.
[0120] Optionally, the battery may be a lithium-ion battery, but is not limited thereto, and the battery may also be a sodium-ion battery, a magnesium-ion battery, etc.
[0121] In one embodiment of the present application, a lithium-ion battery is provided, which includes a positive electrode plate, a negative electrode plate, an electrolyte and a separator, wherein the negative electrode plate is any one of the above negative electrode plates.
[0122] It should be pointed out that the present invention has no particular restrictions on the types or specific components of the positive electrode sheet, electrolyte, isolation membrane, etc., as long as the purpose of this application can be achieved.
[0123] Since the battery provided in the embodiment of the present invention adopts all the technical solutions of the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0124] In order to better understand the present invention, the specific implementation process of the present invention will be described in detail below in a specific implementation mode. The implementation methods described below are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application. If no specific technology or conditions are specified in the implementation method, the technology or conditions described in the literature in the field or the product specification shall be followed.
[0125] Example 1
[0126] The preparation of the negative electrode material comprises the following steps:
[0127] S1. Add graphite 1 (low-oriented graphite), coal tar pitch, and phenolic resin into a VCH mixer at a mass ratio of 20:3:1, and mix at a speed of 2000 r / min for 30 min to obtain a mixture.
[0128] S2. Place the mixture obtained in step S1 in a horizontal granulation kettle and perform low-temperature granulation at 250° C. to obtain a preform.
[0129] S3. The preformed product obtained in step S2 is placed in a tubular furnace in an argon atmosphere and carbonized at 1150° C. for 3 hours to obtain a semi-finished product.
[0130] S4, crushing the semi-finished product obtained in step S3 into a particle size of 7 μm to obtain a soft and hard carbon-coated composite graphite negative electrode material, that is, obtaining a negative electrode material.
[0131] Example 2
[0132] Embodiment 2 is substantially the same as Embodiment 1, except that:
[0133] In step S4, the semi-finished product is crushed to a particle size of 9 μm.
[0134] The rest are the same as in Example 1.
[0135] Example 3
[0136] Embodiment 3 is substantially the same as Embodiment 1, except that:
[0137] In step S4, the semi-finished product is crushed to a particle size of 11 μm.
[0138] The rest are the same as in Example 1.
[0139] Example 4
[0140] Embodiment 4 is substantially the same as Embodiment 1, except that:
[0141] In step S4, the semi-finished product is crushed to a particle size of 13 μm.
[0142] The rest are the same as in Example 1.
[0143] Example 5
[0144] Example 5 is substantially the same as Example 1, except that:
[0145] In step S1, the mass ratio of graphite 1, coal tar pitch and phenolic resin is 30:3:1.
[0146] The rest are the same as in Example 1.
[0147] Example 6
[0148] Embodiment 6 is substantially the same as Embodiment 1, except that:
[0149] In step S1, the mass ratio of graphite 1, coal tar pitch and phenolic resin is 25:3:1.
[0150] The rest are the same as in Example 1.
[0151] Example 7
[0152] Example 7 is substantially the same as Example 1, except that:
[0153] In step S1, the mass ratio of graphite 1, coal tar pitch and phenolic resin is 15:3:1.
[0154] The rest are the same as in Example 1.
[0155] Example 8
[0156] Example 8 is substantially the same as Example 1, except that:
[0157] In step S1, the mass ratio of graphite 1, coal tar pitch and phenolic resin is 20:3.5:0.5.
[0158] The rest are the same as in Example 1.
[0159] Example 9
[0160] Example 9 is substantially the same as Example 1, except that:
[0161] In step S1, the mass ratio of graphite 1, coal tar pitch and phenolic resin is 20:2.5:1.5.
[0162] The rest are the same as in Example 1.
[0163] Example 10
[0164] Embodiment 10 is substantially the same as Embodiment 1, except that:
[0165] In step S1, the mass ratio of graphite 1, coal tar pitch and phenolic resin is 20:2:2.
[0166] The rest are the same as in Example 1.
[0167] Embodiment 11
[0168] Example 11 is substantially the same as Example 1, except that:
[0169] In step S1 , low-oriented graphite 2 is selected to replace graphite 1 .
[0170] The rest are the same as in Example 1.
[0171] Example 12
[0172] Example 12 is substantially the same as Example 1, except that:
[0173] In step S1 , highly oriented graphite 3 is selected to replace graphite 1 .
[0174] The rest are the same as in Example 1.
[0175] Example 13
[0176] Example 13 is substantially the same as Example 1, except that:
[0177] In step S1 , highly oriented graphite 4 is selected to replace graphite 1 .
[0178] The rest are the same as in Example 1.
[0179] It should be noted that, relatively speaking, highly oriented graphite refers to D OI Graphite with relatively high value, low-oriented graphite refers to D OI Graphite with relatively low value. In this application, D OI The value range is 2 to 7. For example, the D of highly oriented graphite OI The value of can be 4.5 to 7. The D OI The value of can be 2 to 4.5. The higher the orientation degree, the worse the fast charging performance and the better the cycle performance. In the above-mentioned embodiments 1, 11, 12 and 13, graphite 1 and graphite 2 are low-oriented graphites, and graphite 3 and graphite 4 are high-oriented graphites. That is, the difference between graphite 1, graphite 2, graphite 3 and graphite 4 is mainly that D OI The specific D values of graphite 1, graphite 2, graphite 3 and graphite 4 (as well as graphite 5 and graphite 6 described below) are different. OI See Table 1 below for values.
[0180] Comparative Example 1
[0181] Comparative Example 1 is substantially the same as Example 1, except that:
[0182] In step S4, the semi-finished product is crushed to a particle size of 4 μm.
[0183] The rest are the same as in Example 1.
[0184] Comparative Example 2
[0185] Comparative Example 2 is substantially the same as Example 1, except that:
[0186] In step S4, the semi-finished product is crushed to a particle size of 24 μm.
[0187] The rest are the same as in Example 1.
[0188] Comparative Example 3
[0189] Comparative Example 3 is substantially the same as Example 1, except that:
[0190] In step S1, the mass ratio of graphite 1, coal tar pitch and phenolic resin is 80:3:1.
[0191] The rest are the same as in Example 1.
[0192] Comparative Example 4
[0193] Comparative Example 4 is substantially the same as Example 1, except that:
[0194] In step S1, the mass ratio of graphite 1, coal tar pitch and phenolic resin is 8:3:1.
[0195] The rest are the same as in Example 1.
[0196] Comparative Example 5
[0197] Comparative Example 5 is substantially the same as Example 1, except that:
[0198] In step S1, the mass ratio of graphite 1, coal tar pitch and phenolic resin is 20:1:3.
[0199] The rest are the same as in Example 1.
[0200] Comparative Example 6
[0201] Comparative Example 6 is substantially the same as Example 1, except that:
[0202] In step S1, the mass ratio of graphite 1, coal tar pitch and phenolic resin is 20:4:0.
[0203] The rest are the same as in Example 1.
[0204] Comparative Example 7
[0205] Comparative Example 7 is substantially the same as Example 1, except that:
[0206] In step S1 , low-oriented graphite 5 is selected to replace graphite 1 .
[0207] The rest are the same as in Example 1.
[0208] Comparative Example 8
[0209] Comparative Example 8 is substantially the same as Example 1, except that:
[0210] In step S1 , highly oriented graphite 6 is selected to replace graphite 1 .
[0211] The rest are the same as in Example 1.
[0212] Performance Testing
[0213] 1. Assemble the negative electrode materials obtained in the above embodiments and comparative examples into a lithium secondary battery. Specifically:
[0214] (1) Preparation of negative electrode sheets: First, prepare negative electrode slurry. The ratio of negative electrode material, conductive carbon black, CMC and SBR in the negative electrode slurry is 93:2:2:3, and the solid content is 50%. The specific preparation method of the negative electrode slurry is as follows: add deionized water, conductive carbon black and 70% of CMC powder to a stirring tank, stir at a low speed for 2 hours to form a conductive glue; add negative electrode material to the conductive glue, stir at a low viscosity and high speed for 1 hour to form a first mixed solution; add SBR to the first mixed solution, stir at a high viscosity and high speed for 1 hour to form a second mixed solution; add ethanol and the remaining 30% of CMC powder to the second mixed solution, stir at a low viscosity and high speed for 2 hours to prepare negative electrode slurry. The ratio of deionized water to ethanol in the slurry is 9:1. The negative electrode material is selected according to the principle in Table 1, or a mixture of the negative electrode material and other active materials in different mass ratios. The specific composition of the negative electrode active material in each embodiment and comparative example is shown in Table 1. The negative electrode slurry is evenly coated on both sides of the negative electrode collector copper foil, dried in an oven, and then cold pressed and cut to obtain the negative electrode sheet.
[0215] (2) Preparation of positive electrode sheets: The positive electrode active material ternary material NCM811, the conductive agent carbon nanotubes, and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 94:3:3, and a solvent N-methylpyrrolidone (NMP) is added. The mixture is stirred evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on both sides of the positive electrode collector aluminum foil, dried in an oven, and then cold pressed and cut to obtain a positive electrode sheet.
[0216] (3) Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent at a concentration of 1 mol / L to obtain an electrolyte after it is fully dissolved.
[0217] (4) Preparation of isolation membrane: A polyethylene film was selected as the isolation membrane.
[0218] (5) Assembly of lithium secondary batteries: stack the positive electrode sheet, separator, and negative electrode sheet in order, with the separator between the positive and negative electrode sheets to serve as an isolation, and then wind to obtain a bare cell; place the bare cell in an outer packaging shell, inject electrolyte after drying, and obtain a lithium secondary battery after vacuum packaging, standing, forming, shaping, and other processes.
[0219] 2. Conducting electrochemical performance tests on the prepared lithium secondary battery, including:
[0220] (1) Dynamic performance (fast charging capability) test: At 25°C, the lithium secondary batteries prepared in the above embodiments and comparative examples were fully charged at a 4C rate and fully discharged at a 1C rate for 10 times, and then the lithium ion battery was fully charged at a 4C rate, and then the negative electrode plate was disassembled and the lithium deposition on the surface of the negative electrode plate was observed. Among them, the area of lithium deposition on the surface of the negative electrode plate is less than 5%, which is considered to be slight lithium deposition, the area of lithium deposition on the surface of the negative electrode plate is 5% to 40%, which is considered to be moderate lithium deposition, and the area of lithium deposition on the surface of the negative electrode plate is greater than 40%, which is considered to be severe lithium deposition.
[0221] (2) Cycle performance test: At 25° C., the lithium secondary batteries prepared in the above embodiments and comparative examples were charged at a 2C rate and discharged at a 1C rate, and a full charge and discharge cycle test was performed until the capacity of the lithium secondary battery decayed to 80% of the initial capacity, and the number of cycles was recorded.
[0222] The test results are shown in Table 1.
[0223] 3. Next, the performance testing method of the negative electrode materials in the embodiments and comparative examples is described.
[0224] (1) The thickness H of the carbon coating layer in the negative electrode material was obtained by using a JEM-2100Plus transmission electron microscope. The powder sample was prepared into a transparent thin sheet and transferred to a TEM mesh slide. The sample was fixed on the mesh slide using acetone. The mesh slide was then placed in a TEM sample box. The sample was subjected to TEM testing at an accelerating voltage of 300 kV to obtain the carbon coating thickness data of the powder.
[0225] (2) Raman spectrum of negative electrode materials I D / I G Data S: obtained by using LabRAM Raman spectrometer. The sample is placed in the test area and 2000 points are accurately scanned in the area of 100μm×100μm. Each point is measured at 1300cm -1 ~1420cm -1 Peak intensity in the wavenumber range I D With 1540cm -1 ~1620cm -1 Peak intensity in the wavenumber range I G The ratio I D / I G The data is recorded as S.
[0226] (3) OI value D of negative electrode material OI:The X-ray powder diffractometer (X'pert PRO) was used to obtain the X-ray diffraction spectrum according to the general rules of X-ray diffraction analysis and the lattice parameter determination method of graphite JIS K 0131-1996 and JB / T4220-2011, and the OI value of graphite was calculated according to the formula VOI=C004 / C110, wherein C004 is the peak area of the 004 characteristic diffraction peak, and C110 is the peak area of the 110 characteristic diffraction peak.
[0227] (4) Volume median particle size D of negative electrode material v50 : Obtained by using a laser diffraction particle size analyzer (MS2000), the sample particles are dispersed in a liquid medium at a concentration of 200-300 mg / L, and a monochromatic light beam is passed through. After the light is scattered by the particles, it is distributed at different angles. The regular multi-element detector receives the values of the scattering diagram at many angles and records these values for analysis. Using the Rayleigh scattering formula, the scattering values are calculated to obtain the ratio of the volume of particles of each size level to the total volume, thereby obtaining the volume distribution of the particle size.
[0228] Table 1 below shows the parameters and test results of Examples 1 to 13 and Comparative Examples 1 to 8 of the present application.
[0229] Table 1
[0230]
[0231]
[0232] It can be seen from Table 1 that compared with Comparative Examples 1 to 8, the lithium batteries using the negative electrode materials prepared in Examples 1 to 13 of the present invention have both good kinetic performance (fast charging capability) and cycle performance. This shows that when the thickness H of the carbon coating layer in the negative electrode material and the Raman spectrum I D / I G Value S, OI value D OI and volume median particle size D v50 Satisfy 0.1≤H×S / D OI ×D v50 When ≤1, the kinetic performance and cycle performance of the negative electrode material, namely the composite graphite, are both excellent. This is due to the good particle size of the composite graphite, the appropriate thickness and disorder of the carbon coating layer, and the excellent crystal orientation. Since the surface of the negative electrode material has sufficient lithium insertion active sites, the overall material is close to an isotropic structure, and the number of surface defects of the material is also small, the prepared battery has excellent comprehensive performance.
[0233] Specifically, when the volume median particle size D of the negative electrode material v50 Too small or the carbon coating thickness H is too thick or the Raman spectrum of composite graphite I D / IG The value S is too large or the OI value of the composite graphite is D OI Too small results in H×S / D OI ×D v50 When the upper limit is exceeded, the cycle performance of lithium-ion batteries is poor. This is because when the volume median particle size D v50 When the thickness H of the carbon coating layer on the graphite surface is too thick, the proportion of amorphous carbon components on the graphite surface is too high, which will also lead to too many defects on the graphite surface, aggravating the side reactions between graphite and electrolyte during the cycle and causing irreversible capacity loss. The number of cycles in comparative example 4 is only 1663. When the Raman spectrum of graphite I D / I G When the value S is too large, the disorder degree of the carbon coating on the graphite surface is high, the defect components are more, the battery side reactions are more during the cycle, and the cycle performance is poor. The number of cycles of comparative example 5 is only 1589. Finally, if the OI value of graphite is too small, the number of defects on the graphite surface will increase, resulting in a decrease in battery cycle performance. The number of cycles of comparative example 7 is only 1947.
[0234] When the volume median particle size D of the negative electrode material v50 Too large or the carbon coating thickness H is too thin or the Raman spectrum of composite graphite I D / I G The value S is too small or the OI value D of the composite graphite OI Too large leads to H×S / D OI ×D v50 When the lower limit is exceeded, the fast charging performance of lithium-ion batteries is poor. This is because when the volume median particle size D v50 When the thickness H of the carbon coating layer on the graphite surface is too thin, the amorphous carbon component on the graphite surface is small, the number of active sites for lithium insertion is small, and the charge transfer impedance is high. The kinetic performance test result of Comparative Example 3 is severe lithium precipitation. When the Raman spectrum of graphite I D / I G When the value S is too small, the disorder degree of the graphite surface coating layer is low, resulting in fewer active sites for lithium insertion on the graphite surface. The kinetic performance test result of comparative example 6 is severe lithium precipitation. OI When it is too large, the microcrystals in the graphite particles are arranged nearly in parallel, and the macroscopic appearance is an anisotropic structure. The number of end faces available for lithium ion embedding is small, resulting in poor fast charging performance of the battery. The kinetic performance test results of Comparative Example 8 show severe lithium plating.
[0235] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0236] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.
[0237] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0238] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0239] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A negative electrode material, characterized in that: The negative electrode material comprises a graphite core and a carbon coating layer coated on at least a portion of the surface of the graphite core, wherein the carbon coating layer comprises soft carbon and hard carbon; The thickness of the carbon coating layer is H; In the Raman spectrum, the negative electrode material has a carbon characteristic peak D and a carbon characteristic peak G, and the peak intensity of the carbon characteristic peak D is D The peak intensity I of the carbon characteristic peak G G The ratio I D / I G is S; The OI value of the negative electrode material is D OI ; The median particle size of the negative electrode material is D v50 ; H, S, D OI and D v50 satisfy: 0.1≤H×S / D OI ×D v50 ≤1。 2. The negative electrode material according to claim 1, characterized in that H, S, D OI and D v50 Fabric meets: 0.2≤H×S / D OI ×D v50 ≤0.8。 3. The negative electrode material according to claim 1, characterized in that The value range of H is 70nm to 150nm; and / or, the D v50 The value range is 6μm~14μm.
4. The negative electrode material according to claim 1, characterized in that The value range of S is 10% to 20%.
5. The negative electrode material according to claim 1, characterized in that The D OI The value range is 2 to 7.
6. The negative electrode material according to any one of claims 1 to 5, characterized in that: The mass ratio of the soft carbon to the hard carbon is 10:1 to 2:
1.
7. The method for preparing a negative electrode material according to any one of claims 1 to 6, characterized in that: The method comprises: mixing graphite, a soft carbon precursor, and a hard carbon precursor to obtain a mixture; granulating the mixture to obtain a preform; The preform is carbonized and then crushed to a target particle size to obtain a negative electrode material.
8. The method for preparing the negative electrode material according to claim 7, characterized in that: The soft carbon precursor includes at least one of coal tar pitch or petroleum pitch; and / or, the hard carbon precursor comprises at least one of phenolic resin, polyacrylonitrile, chitosan, epoxy resin, sucrose or polyvinyl pyrrolidone; and / or, the mass ratio of the graphite to the soft carbon precursor is 20:2 to 20:4; and / or, the mass ratio of the graphite to the hard carbon precursor is 30:1 to 30:3; And / or, the granulation temperature is 200°C to 300°C; And / or, the carbonization temperature is 1000°C to 1300°C.
9. A negative electrode plate, characterized in that: The negative electrode plate comprises a current collector and a negative electrode film layer arranged on the surface of the current collector; The negative electrode film layer comprises the negative electrode material according to any one of claims 1 to 6 or the negative electrode material prepared by the method according to any one of claims 7 to 8.
10. A battery, characterized in that: The battery comprises the negative electrode material according to any one of claims 1 to 6, or comprises the negative electrode material prepared by the method according to any one of claims 7 to 8, or comprises the negative electrode plate according to claim 9.
Citation Information
Patent Citations
Hard carbon-coated graphite negative electrode material, lithium ion battery, and preparation method and application thereof
CN111244401A
Cited By
Negative plate, battery and electric equipment
CN121237819A
Negative electrode sheet, battery, and electric device
WO2026194828A1